2008
DOI: 10.1007/s00425-008-0872-4
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic surface of dividing cyanelles and ultrastructure of the region directly below the surface in Cyanophora paradoxa

Abstract: The cyanelles of glaucocystophytes are probably the most primitive of known extant plastids and the closest to cyanobacteria. Their kidney shape and FtsZ arc during the early stage of division define cyanelle division. In order to deepen and expand earlier results (Planta 227:177-187, 2007), cells of Cyanophora paradoxa were fixed with two different chemical and two different freeze-fixation methods. In addition, cyanelles from C. paradoxa were isolated to observe the surface structure of dividing cyanelles us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The FtsZ ring and the inner PD ring were detected at the chloroplast division site (41,42). However, the outer PD ring was not evident (41,42), and DRP5B is not encoded in the C. paradoxa genome (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FtsZ ring and the inner PD ring were detected at the chloroplast division site (41,42). However, the outer PD ring was not evident (41,42), and DRP5B is not encoded in the C. paradoxa genome (43).…”
Section: Discussionmentioning
confidence: 99%
“…The FtsZ ring and the inner PD ring were detected at the chloroplast division site (41,42). However, the outer PD ring was not evident (41,42), and DRP5B is not encoded in the C. paradoxa genome (43). It has been suggested that the constriction of the division site is accompanied by an ingrowth and subsequent degradation of the PG layer at the division site in glaucophyte chloroplast division, as in bacterial cell division (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…FE-SEM was performed as described by Sato et al (2009) with minor modifications. Cells were subjected to double fixation using 2% glutaraldehyde and 1% osmium tetroxide as described previously (Matsuzaki et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Sato et al (2009) showed the clear plastid surface of C. paradoxa under ultra-high resolution FE-SEM. However, the surface ornamentations of the vegetative cells of Cyanophora have not been examined using ultra-high resolution FE-SEM.…”
mentioning
confidence: 96%
“…A recent study of MreBCD depletion mutants growing as large spheres provides convincing evidence for asymmetric constriction, with the constriction located at an arc of FtsZ (11). A dramatic example of asymmetric septation is seen in the division of the cyanelle, a primitive plastid of the protist Cyanophora paradoxa (165,166). The Z ring extends from onefourth to one-half way around the cell and is located over a very asymmetrically forming septum (Fig.…”
Section: Incomplete Ftsz Rings Can Generate Constrictionmentioning
confidence: 99%